Emerging trends in enzyme inhibition by multivalent nanoconstructs. Issue 39 (4th September 2015) - Kanfar, Nasreddine; Bartolami, Eline; Zelli, Renaud; Marra, Alberto; Winum, Jean-Yves; Ulrich, Sébastien; Dumy, Pascal
Abstract : This review highlights the recent implementation of multivalent nanoconstructs in enzyme inhibition and discusses the emerging trends in their design and identification. Abstract : Multivalent nanoconstructs, extensively used for enhancing the recognition of biomolecular targets, have been recently exploited for enzyme inhibition showing interesting properties such as improvement of inhibitory potency and selectivity. We review herein the recent results highlighting the potential of multivalent nanoconstructs for the inhibition of different enzymes, and the emerging trends in the generation and identification of multivalent clusters as enzyme inhibitors.